(untitled) (CIPEEX, 2025)
Strength training is still understudied when compared to aerobic exercise and its relationship with blood pressure. Therefore, further research on this subject is necessary. This study aimed to evaluate blood pressure response after strength training for upper and lower limbs in normotensive young adults. This is a controlled experimental study that evaluated 80 individuals. They performed one exercise session for upper limbs (UL), one for lower limbs (LL), and one control session (CS). Blood pressure was measured between exercise sets and up to 20 minutes after completion. In the control session, there were no exercises, but blood pressure was measured. Descriptive statistics were performed using the nonparametric Wilcoxon test. Significance was set at p≤ 0.05, and the program used was SPSS 10. Pre-exercise blood pressure results were not significant, but post-exercise there were significant changes in SBP and DBP levels. There was a greater increase in leg exercises than in arm exercises. Thus, it was concluded that there was a greater increase in BP in the leg protocols than in the arm protocols.